2017
DOI: 10.1051/0004-6361/201730823
|View full text |Cite
|
Sign up to set email alerts
|

Flux decay during thermonuclear X-ray bursts analysed with the dynamic power-law index method

Abstract: The cooling of type-I X-ray bursts can be used to probe the nuclear burning conditions in neutron star envelopes. The flux decay of the bursts has been traditionally modelled with an exponential, even if theoretical considerations predict power-law-like decays. We have analysed a total of 540 type-I X-ray bursts from five low-mass X-ray binaries observed with the Rossi X-ray Timing Explorer. We grouped the bursts according to the source spectral state during which they were observed (hard or soft), flagging th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Traditionally, X-ray burst decays have been described with an exponential function, but when high signal to noise ratio data are analyzed, a power-law decay is often a better description and sometimes complex shapes are observed (e.g. in 't Zand et al 2014a;Kuuttila et al 2017). The duration of X-ray bursts commonly ranges from several seconds up to several minutes, and the total radiated output is typically ∼ 10 39 erg (e.g.…”
Section: Type-i X-ray Burstsmentioning
confidence: 99%
“…Traditionally, X-ray burst decays have been described with an exponential function, but when high signal to noise ratio data are analyzed, a power-law decay is often a better description and sometimes complex shapes are observed (e.g. in 't Zand et al 2014a;Kuuttila et al 2017). The duration of X-ray bursts commonly ranges from several seconds up to several minutes, and the total radiated output is typically ∼ 10 39 erg (e.g.…”
Section: Type-i X-ray Burstsmentioning
confidence: 99%
“…The exception to this rule is for bursts for which it is more or less certain that there is no H present in the burning layer, like in 4U 1820-30. Kuuttila et al (2017) found perhaps marginal evidence for α evolution in that source, as judged from their Fig. 3, for the phases where dynamical effects (PRE) are negligible.…”
Section: Discussionmentioning
confidence: 87%
“…11); 2) for Eddington-limited bursts (i.e., bursts with photospheric radius expansion or 'PRE') from 4U 1636-526 and 4U 1608-52, the same applies (although at different α values); 3) there are strong α evolutions for all bursts from GS 1826-24 and non-PRE bursts from 4U 1636-536 and 4U 1608-52; 4) below one-third to onefifth of the peak flux, the α profile is flatter for bursts detected in the hard state than in the soft state. Interestingly, Kuuttila et al (2017) directly compared the α evolution with the theoretical predictions from in 't and found that they are generally inconsistent for fluxes above one-third of the peak flux and marginally consistent below this, with the exception of GS 1826-24, which is strongly inconsistent throughout. In our opinion, both studies (Kuuttila et al 2017 and ours) show that a large portion of the signal in the decay phase of many bursts is due to rp processing and that the difference between PRE and non-PRE bursts is due to a difference in H abundance in the burning layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations